2014
DOI: 10.3748/wjg.v20.i39.14142
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B and liver transplantation: Molecular and clinical features that influence recurrence and outcome

Abstract: Hepatitis B virus (HBV) continues to be a major cause of morbidity and mortality worldwide. It is estimated that about 350 million people throughout the world are chronically infected with HBV. Some of these people will develop hepatic cirrhosis with decompensation and/or hepatocellular carcinoma. For such patients, liver transplantation may be the only hope for cure or real improvement in quality and quantity of life. Formerly, due to rapidity of recurrence of HBV infection after liver transplantation, usuall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 75 publications
0
18
0
Order By: Relevance
“…The 1762 and 1764 mutations reduce transcription of the PC mRNA by interfering binding of transcription factors, which in turn downregulates HBeAg synthesis. Some studies have shown that genomic mutations at positions 1727G, 1741C, 1761C, 1757A /1764T /1766G, 1773T, 1773T /1775G and 1909C are associated with HCC in HBV-infected patients (15)(16)(17)(18)(19). Several studies have reported an association between CP mutations and increased risk of liver inflammation, cirrhosis (20) and HCC (21).…”
Section: Resultsmentioning
confidence: 99%
“…The 1762 and 1764 mutations reduce transcription of the PC mRNA by interfering binding of transcription factors, which in turn downregulates HBeAg synthesis. Some studies have shown that genomic mutations at positions 1727G, 1741C, 1761C, 1757A /1764T /1766G, 1773T, 1773T /1775G and 1909C are associated with HCC in HBV-infected patients (15)(16)(17)(18)(19). Several studies have reported an association between CP mutations and increased risk of liver inflammation, cirrhosis (20) and HCC (21).…”
Section: Resultsmentioning
confidence: 99%
“…Among viral hepatitis such as chronic HBV infection, the liver transplant is also considered as the final treatment method, which leads to rejection or acceptance of liver graft (3)(4)(5)(6)(7). Accordingly, activation of inflammatory signaling pathways is reported in allograft rejection.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of possible determinative association between pathogenesis of chronic hepatitis B virus (HBV) infection with IRFs, limited studies were accomplished (15). Chronic HBV infection can lead to the end-stage liver diseases such as hepatocellular carcinoma and cirrhosis (3)(4)(5)(6)(25)(26)(27). Therefore, early prognosis of any change in immune factors such as IRFs molecules leads to better management of post-liver transplant outcomes and raises the possibility of graft survival.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatitis B virus (HBV) remains a major cause of morbidity and mortality worldwide (1). It has been estimated that ~350 million individuals worldwide are chronically infected with HBV.…”
Section: Introductionmentioning
confidence: 99%
“…It has been estimated that ~350 million individuals worldwide are chronically infected with HBV. A proportion of these patients will subsequently develop hepatic cirrhosis, so therapy to control active inflammation is important (1). The key to effective treatment is to inhibit the replication of HBV and prevent it from progressing to cirrhosis, hepatic failure and hepatic cell cancer (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%